The comparative efficiency of the carbohydrate exchange regulation in rats with experimental diabetes mellitus by natural adaptogens - Hubich, Aksana I.; Kapaneva, Anastasiya P.; Burak, Alena V. (Experimental Biology and Biotechnology, 2019)
This work is devoted to the study of the efficiency of the carbohydrate metabolism biochemical markers correction in laboratory rats with experimental diabetes mellitus by some natural adaptogens (Sideritis scardica, Stevia rebaudiana, Zingiber officinale, Schisandra chinensis (Turcz.) Baill, Hibiscus sabdariffa, mumijo). It is shown that the use of all the drugs studied in rats with experimental diabetes mellitus contributes to the partial normalization of carbohydrate metabolism markers’ values (a-amylase activity, glucose concentration, pyruvate content). The action of broths of Schisandra chinensis and Zingiber officinale was the most pronounced, it exceeded the effect of the anti-diabetic «Sadifit» collection. The results obtained may be due to the presence of flavonoids, vitamins A, C, E and unsaturated fatty acids exhibiting an antioxidant effect in the plant composition, as well as glycosides of schisandrene and schisandrole (Schisandra chinensis) and sesquiterpine zingiberine (Zingiber officinale), which increase the permeability of the cell membrane for glucose.